Detection of lead (pb) and aluminum (Al) metal as contaminant in food prepared by using locally manufactured cooked pots (Hala) in Kosti City, Sudan - Salah, EI; Eltayebb, TEM; Sabahelkhier, MK; Abuseif, HM (International Journal of Environment, 2015)
The objectives of this study are to assess the quantities of Aluminu m; lead released into the food from locally manufactured cooked pots (Aluminium pots) in Kosti market. Seven types of pots (Pistons, Cartels, Kettles, Kettles + trays, Pepsi cans, Atmonia and Steel) which is locally manufactured cooked pots (Hala) were used. Amount of Al and Pb that leaked into the food from locally manufactured cooked pots were assessed by using Atomic Absorption Spectroscopy. The results were indicated that highly significance amount of Aluminum and lead which were leaked into the food that prepared by locally manufactured cooked pots (Hala).The analysis of urine for 10 selected randomly individuals that used locally manufactured cooked pots (Hala) for preparation their food were indicated highly amount of Aluminum and Lead in their urine. DOI: http://dx.doi.org/10.3126/ije.v4i2.12621 International Journal of Environment Vol.4(2) 2015: 19-26